Failure to use health services by people with Chagas disease: Multilevel analysis of endemic area in Brazil. - Renata Fiúza Damasceno; Ester Cerdeira Sabino; Antonio Luiz Pinho Ribeiro; Ariela Mota Ferreira; Léa Campos de Oliveira-da Silva; Cláudia Di Lorenzo Oliveira; Clareci Silva Cardoso; Thallyta Maria Vieira; Desirée Sant' Ana Haikal (Public Library of Science (PLoS), 2022)
This study aimed to assess the prevalence of non-use of health services in the last year by people with Chagas disease (CD) in an endemic area in Brazil and the contextual and individual factors associated with this non-use. This is a multilevel study that considered contextual and individual data. Contextual data were collected from official publicly accessible databases of the Brazilian government, at the municipal level. The individual data came from the first follow-up of a Brazilian cohort that assessed patients with CD in 21 municipalities in endemic area for the disease. The sample consisted of 1,160 individuals with CD. The dependent variable "use of health services in the last year" was categorized as yes vs. no. The analysis was performed using Poisson regression with robust variance. The prevalence of non-use of health services in the last year was 23.5% (IC95%: 21.1-25.9). The contextual factor "larger population" (PR: 1.6; 95% CI = 1.2-2.0) and individual factors related to the lower severity of the disease as a functional class without limitations (PR: 1.6; 95% CI = 1.2-2.1) and unaltered N-terminal pro b-type natriuretic peptide levels (PR: 2.2; 95% CI = 1.3-3.6) increased the prevalence of non-use of the health service in the last year by people with CD. The results of this study showed that individual determinants are not isolated protagonists of the non-use of health services in the last year by people with CD, which reinforces the need for public policies that consider the contextual determinants of the use of health services by populations affected by the disease.